(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
It has been well established in this research work that sulphide ion play a crucial role in chalcogenide semiconductor devices. The impact of sulphide ion content (S2-) on the surface morphology, optical, electrical and micro-structural properties of chemically deposited CdZnS nanoparticles was examined. The nanoparticles were prepared using cadmium sulphate as Cd2+ source, zinc sulphate as Zn2+source and thiourea as S2- source. NH4OH was used as the complexing agent. The thiourea concentration was varied between 0.075 M – 0.580 M while the concentration of ZnSO4, CdSO4 and NH4OH were fixed. EDX was used to confirm the compositional elements of the nanoparticles which are Cd2+, Zn2+, S2- and little content of Si and O2. The SEM analysis revealed good uniformity and densely packed structure. Sulphide-rich nanoparticles exhibit large crystallite size compare to sulphide-poor nanoparticles. XRD indicates hexagonal structure (002) without phase transition. S2–rich CdZnS revealed less polycrystallinity compare to S2–poor CdZnS samples which exhibit better polycrystallinity. The crystallite size varied between 10 nm to 52 nm. The dislocation density increases from 0.000852 to 0.00242 Line2/m2 and then decreased to 0.000364 Line2/m2. Other microstructural properties such as lattice parameter and micro-strain as well as their relation with grain boundary surface area were also discussed. The best transmittance of about 97% was revealed. The layers deposited with high S2- content showed less percentage transmittance and exhibit narrow energy band gap. The electrical resistivity is decreased while electrical conductivity increases with increasing S2- content. The sheet resistance, charge carrier mobility and charge carrier density